If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 43 + -1x = 7 Solving 43 + -1x = 7 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-43' to each side of the equation. 43 + -43 + -1x = 7 + -43 Combine like terms: 43 + -43 = 0 0 + -1x = 7 + -43 -1x = 7 + -43 Combine like terms: 7 + -43 = -36 -1x = -36 Divide each side by '-1'. x = 36 Simplifying x = 36
| 1-20n=-20n+1 | | 5(2h+3)=5(h-3) | | 3-18t=-18t+3 | | 14d+10+2d=10+16d | | 3(x+8)=24+3x | | -8-6q=-5q-10 | | X^2-250/x | | -3j+9=-5j-7 | | 2+f=f-1 | | 1/3x^4-2x^3 | | 10p+2=2+10p | | -10-3h=-3h-10 | | 7/5a=-14/3 | | -3+3r=10+3r | | -8w=-5-9w | | -2t+5= | | -24.226674+0.1x=-1.93(1-4.2x) | | 10-x+y+10=40 | | -12+12x-3x^2=0 | | 2x^2+x=420 | | (9/4y)^3*y^2 | | 3/16(x)=150 | | 3/16x=150 | | -3/8u=18 | | 25000-1200y=x | | 6(2x+4)=2(3x+6) | | 6(2+4)=2(3x+6) | | 6(2+4)=(3x+6) | | 1.49(w-4.3)=14.82 | | (5-w)(4w-1)=0 | | 9w+27=6(w+6) | | 10.59=12.7g-3.45-7.3g |